Functional properties and physicochemical characteristics of tamarind (Tamarindus indica L.) seed mucilage powder as a novel hydrocolloid. (September 2017) - Alpizar-Reyes, Erik; Carrillo-Navas, Hector; Gallardo-Rivera, Raquel; Varela-Guerrero, Victor; Alvarez-Ramirez, Jose; Pérez-Alonso, César
Abstract: Tamarind seed mucilage was isolated and dried with spray dryer. Functional properties and physicochemical characteristics of the extracted mucilage were evaluated. Functional properties showed that the solubility, water holding capacity and oil holding capacity increased with temperature. The swelling index was determined at different temperatures (25, 45 and 65 °C) and pH (2, 4, 6, 7 and 8), increasing when these variables were increased. Emulsifying ability increased and emulsifying stability decreased when the weight of powder of tamarind seed mucilage/oil volume ratio was increased. Thermogravimetry showed that mucilage particles were thermostable until 175 °C when an appreciable mass loss began. The morphology of the external surfaces of tamarind seed mucilage particles showed continuous walls with no fissures, cracks or interruptions, semi spherical particles with a skin-like particle structure. Given the similarity of this novel mucilage with commercial hydrocolloids, it could be potentially applied for human consumption industries as functional, cheap and environmental friendly hydrocolloids. Highlights: Functional properties of mucilage powder increased when temperature was increased. Tamarind seed mucilage showed high emulsifying ability (>78%) and stability (>82%). Tamarind seed mucilage particles were thermostable until 175 °C. X-ray of tamarind seed mucilage particles exhibited an amorphous halo. The morphology of mucilage showed continuous walls with polymeric appearance.